Application and Advance of Image Compression Algorithms in Medical Imaging - SHANG Jiawen; HUANG Peng; CHANG Zhixing; FAN Yuhan; HU Zhihui; ZHANG Ke; DAI Jianrong; YAN Hui (Xiehe Yixue Zazhi, 2025)
Medical imaging technology plays a crucial role in clinical diagnosis and treatment. Image compression technology provides robust technical support for the storage and transmission of massive medical imaging data, serving as an effective safeguard for hospital data backup and telemedicine. The technology holds broad application prospects in the medical field, enabling the processing of various imaging modalities, multidimensional imaging, and medical video imaging. This study elaborates on general image and video compression algorithms, the application of compression algorithms in the medical field, and the performance metrics of medical image compression, thereby providing critical technical support for enhancing clinical diagnostic efficiency and data management security.